Matrine inhibits the progression of prostate cancer by promoting expression of GADD45B. Issue 5 (21st January 2018) - Huang, Hai; Wang, Qiong; Du, Tao; Lin, Chunhao; Lai, Yiming; Zhu, Dingjun; Wu, Wanhua; Ma, Xiaoming; Bai, Soumin; Li, Zean; Liu, Leyuan; Li, Qi
Abstract : Background: Matrine is a naturally occurring alkaloid extracted from the Chinese herb Sophora flavescens . It has been demonstrated to exhibit antiproliferative properties, promote apoptosis, and inhibit cell invasion in a number of cancer cell lines by modulating the NF‐κB pathway to downregulate the expression of MMP2 and MM9. It has also been shown to improve the efficacy of chemotherapy when it is combined with other chemotherapy drugs. However, the therapeutic potential of matrine for prostate cancer needs to be further studied. Methods: We analyzed KEGG pathways of differential gene expression between matrine‐treated and untreated prostate cancer cell lines and identified GADD45B as one of major target genes of matrine based on its role in apoptosis and prognosis value for prostate cancer patients in TCGA database. We further analyzed the expression of GADD45B protein in a tissue microarray and mRNA in TCGA database, and tested the synergistic impacts of matrine and GADD45B overexpression on proliferation, apoptosis, migration and invasion of prostate cancer cell DU145. Results: Matrine promoted the expression of GADD45B, a tumor suppressive gene that is involved in the regulation of cell cycle, DNA damage repair, cell survival, aging, apoptosis and other cellular processes through p38/JNK, ROS‐GADD45B‐p38, or other signal pathways. Although GADD45B is elevated in prostate cancer tissues, levels of GADD45B in prostate tumor tissues are reduced at late stage of tumor invasion, and higher levels of GADD45B predict better survivals of prostate cancer patients. Conclusions: Matrine may be used to treat prostate cancer patients to increase the levels of GADD45B to inhibit tumor invasion and improve patient survivals.